Using Augmented Reality-Based e-Book for Improving Students’ Learning Motivation in Analytical Geometry Course - Ngastiti, Pukky Tetralian Bantining; Umam, Ahmad Khairul; Alfan, Aris (Jurnal Pendidikan MIPA, 2022)
In the development of science and technology in the world of education, students need to be introduced to a variety of varied learning media, one of which is the use of augmented reality-based e-books. The ability to learn analytic geometry requires systematic, logical and critical thinking that can be developed through learning. The purpose of this study is to test the increase in learning motivation using augmented reality based e-book media in analytic geometry course. The method in this study using ADDIE which consists of five stages which include analysis, design, development, implementation and evaluation. The result of the research is that the average result of the questionnaire given by students from various aspects of the assessment is 86%. Meanwhile, based on learning outcomes, there is a difference in learning outcomes between midterm exam score and the e-book score, which is 9.18 and based on the results of the analysis using SPSS on the t-test, it is found that tcount = 4.768 > ttable = 2.015. From these results, it can be concluded that augmented reality-based e-book media in analytic geometry courses can motivate students as a technology based learning medium for students of mathematics study program at Universitas Billfath. Keywords: augmented reality, geometry analytic, e-book DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp486-495